Communion with God and the Brothers: Reading Rancé - Caneva, Anna Maria (Cistercian studies quarterly, 2003)
Presents a series of texts from the book 'On the Holiness and Duties of Monastic Life' written by Rancé. Definition of a monk; Idea of religious vows; Value of community life.